Synthesis and Characterization of Castor Oil-Based Polyurethane Nanocomposites - Wong, Kai Yi; Gan, Seng Neon; Teh, Geok Bee; Sin, Sau Leng (Wiley-VCH Verlag, 2018)
A series of castor oil-based polyurethane (PU) with and without the incorporation of Halloysite nanoclay as filler are synthesized via addition polymerization of polycaprolactone-diol (PCL) and methylene diphenyl diisocyante (MDI) as monomers. The PUs are characterized by using attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), thermogravimetric anaysis (TGA), differential scanning calorimetry (DSC), scanning electron microscope (SEM), and pencil hardness test. The TGA thermogram showed that the incorporation of castor oil affected the thermal stability of the PU matrices by 7–9% in reduction of the decomposition temperature; whereas the incorporation of Halloysite nanoclay into the PU matrices increased the thermal stability by 3–5% in the detection of higher decomposition temperature. The DSC thermograms of the castor-oil based PU and castor oil-based PU with Halloysite nanoclay showed reduction in glass transition temperature (Tg) by 13–33 and 8–14 °C, respectively as compared to pristine PU and castor-oil based PU. It is envisaged that the reduction in Tg is caused by the non-uniformity of dispersion of the Halloysite nanoclay throughout the PU matrices and hence, affected the mobility of the PU chains. The SEM images further confirmed the non-uniformity of dispersion of the Halloysite nanoclay in the PU films. Pencil hardness test indicated that the PU films coated on glass slides had lower than 1H hardness.